Implementasi Fundraising Program KOIN NU di Lembaga NU-CARE LAZISNU Kecamatan Kamal Bangkalan - Fitriyani, Endang; Faraby, Muhammad Ersya (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
This study aims to identify the application of the system in the KOIN NU work programme which is channeled through the permanent compensation work programme (SANTAP) at the NU-CARE LAZISNU institution in Kamal Bangkalan District. This research is a qualitative study that focuses on direct human behaviour, with a field research method that requires researchers to go directly to the research location to collect the required data. The results of this study reveal that NU-CARE LAZISNU Kamal Bangkalan Sub-district has successfully implemented the KOIN NU work programme through Fundraising activities. The Fundraising process involves steps such as mapping the placement of KOIN NU cans, determining KOIN officers, and implementing the SANTAP work programme as part of the administration of donated funds. Supporting factors for the success of the KOIN NU movement include systematic data collection of donors, active participation of the community who are very loyal in giving, and high enthusiasm reflected in most of the community. However, the research also identified several obstacles faced by NU-CARE LAZISNU Kamal Bangkalan District, especially in the aspect of human resources. Many administrators and officers are not fully loyal in carrying out their duties, and the placement of KOIN NU cans has not been evenly distributed throughout the community of Kamal Bangkalan Sub-district. Keywords: Fundraising, KOIN NU, MWCNU Kamal